PENGARUH RESIKO BISNIS DAN RESIKO KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan PT. Astra Internasional Tbk. dan PT. Tambang Batubara Bukit Asam Tbk.) - Adri Wihananto (Jurnal Ilmiah Binaniaga, 2011)
The aim of this research is to analyse relevantly of business risk and financial risk, is have influence and relation, or not with value of company. If in research process found by inexistence of relation and influence from business risk and financial risk, so will searching that problem and searching the othe factors perhaps existence relation and influence to value of companies. The research object are business risk, financial risk, and intrinsic value of companies from PT. Astra Internasional Tbk., and PT. Tambang Batubara Bukit Asam Tbk, case study. The research shows that in PT. Astra Internasional Tbk, influential business risk according to significant towards value of companies, that is with level significant as big as 0,049. While in PT. Tambang Batubara Bukit Asam Tbk, business risk not influential according to significant towards value of companies, that is with level significant as big as 0,980. In PT. Astra International Tbk, influential finance risk according to significant towards value of companies, that is with level significant as big as 0,075. While in PT. Tambang Batubara Bukit Asam Tbk, finance risk not influential according to significant towards value of companies, that is with level significant as big as 0,735. Result of evaluation in this research is that value of companies do not only be influenced by factor of business risk and financial risk of Company. but there is other factor which can influence such as efficiency cost factor, company performance and company dividen policy. Keyword : Business risk, Financial risk, Value of company